Socio Technical Impact of Broadband Services in Baluchistan - Ahthasham, Saira; Shaikh, Aftab Ahmed; Iqbal, Muhammad; Sajid, Ahtsham; Shahzad, Amir (International Journal of Engineering and Technology, 2012)
Broadband infrastructure is a key component of knowledge economy. Broadband service both on fixed and mobile networks are becoming an indicator of the knowledge economy. Globally it is viewed that countries with developed broadband infrastructures are working more efficiently and effectively towards social and economic growth. To achieve worldwide broadband connectivity level Government of Pakistan and industry must play a combine role for the betterment and improvement of the said industry. Government and market players must come up with innovative broadband packages that can capture the customer demand. This paper analysis market trends, customer expectation and socio-technical impact of broadband service in Baluchistan.